2018
DOI: 10.3390/condmat3040050
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Characterization of Stone–Wales Defects on Graphene Quantum Dot: A First-Principles Study

Abstract: A first principles based density functional theory (DFT) has been employed to identify the signature of Stone-Wales (SW) defects in semiconducting graphene quantum dot (GQD). Results show that the G mode in the Raman spectra of GQD has been red shifted to 1544.21 cm −1 in the presence of 2.08% SW defect concentration. In addition, the intensity ratio between a robust low intense contraction-elongation mode and G mode is found to be reduced for the defected structure. We have also observed a Raman mode at 1674.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 55 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…They conclude that such results are very valid and will indeed operate as a valuable reference for the possible application of GQD-based nanodevices (including inherent topological SW defect) to experimental systems. [122] Recently (in 2019), Zhou and co-workers showed a thorough DFT study on the effect of the SW defects and 3d TM (scandium (Sc), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), and copper (Cu)) dopants on arsenene by describing the structural, magnetic, and electronic features. Such influential features have been efficiently changed by SW defect and TM doping.…”
Section: Structural Electronic Magnetic and Spectroscopic Feature Ana...mentioning
confidence: 99%
“…They conclude that such results are very valid and will indeed operate as a valuable reference for the possible application of GQD-based nanodevices (including inherent topological SW defect) to experimental systems. [122] Recently (in 2019), Zhou and co-workers showed a thorough DFT study on the effect of the SW defects and 3d TM (scandium (Sc), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), and copper (Cu)) dopants on arsenene by describing the structural, magnetic, and electronic features. Such influential features have been efficiently changed by SW defect and TM doping.…”
Section: Structural Electronic Magnetic and Spectroscopic Feature Ana...mentioning
confidence: 99%
“…This further indicates that a slight variation in the morphology of the structure due to SW defects may result in significant modifications of physical properties. 30,32 Interestingly, the C 1 -and C 6 -type atoms of phagraphene become equivalent in the defective structures, resulting in an increased symmetry of the defected structures. It is expected that the interchange in the role of inequivalent and equivalent carbon atoms may lead to some exotic behavior of the electronic properties of the system.…”
Section: Acsmentioning
confidence: 99%
“…30 Moreover, tuned electronic and enhanced transport properties have been observed in SW-defective graphene nanoribbons 31 quantum dots. 32 Particularly, SW defects are very important due to their moderate energy cost, and no atom is lost during the process. Such defects are experimentally viable to form during the growth process.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Chakraborti et al have found that an increase in the concentration of SW defects in GQDs results in a decrease in the electrical conductivity of GQDs. 31 Moreover, some studies have reported that defects induced heteroatom doping, such as nitrogen and sulfur dopants, can reduce the band gap of GQDs, leading to improve light absorption and prolonged luminescence lifetime. 24,[32][33][34][35][36][37][38] In addition, the presence of defects in GQDs has been exploited for specic applications.…”
Section: Introductionmentioning
confidence: 99%